The Concept and Classification of Phraseology in English Language - qizi, Dushatova Shohsanam Baxtiyor; qizi, Jumanaliyeva Dildora Abdulhamid (International Journal on Integrated Education, 2023)
Phraseological units can be classified according to their various signs from the point of view of modern linguistics. Phraseological units are divided into categories according to their etymological, structural-semantic, and motivational meaning, according to which word group they are expressed in linguistic works. The fund of Uzbek phraseology is filled with national and adopted, terminological and non-terminological units as phraseology in English.